Thirty years of declining stunting in Tanzania: Trends and ongoing challenges - Ester Elisaria; Bet Caeyers; Esther Nkuba; Laura van der Erve; August Kuwawenaruwa (PLoS ONE, 2025)
Background Tanzania has made considerable gains in children’s nutrition between 1991/92 and 2022. The country’s stunting rate has decreased from 50% in 1992 to 30% in 2022. However, stunting varies greatly among regions. The purpose of this study was to examine regional trends in stunting rates and associated characteristics related to the risk of being stunted among children under the age of five in Tanzania. Methods Descriptive statistics were used to summarize the data on stunting, from the Tanzania Demographic and Health Survey (TDHS) data. A total of 42,408 under-five children from repeated TDHS cross-sectional studies conducted in 1991–1992 (n = 6,585), 1996 (n = 5,438), 1999 (n = 2,555), 2004–2005 (n = 7,230), 2009–2010 (n = 6,792), 2015–2016 (n = 9,001), and 2022 (n = 4,807) were analysed to examine trends in stunting and its associated characteristics in the country. Frequencies and percentages were calculated and presented in tables and graphs as cross-sectional data points. A multivariable logistic regression model was estimated to identify factors associated with stunting in 2022. All analyses have been weighted using the weighting generated by the TDHS. STATA version 15 was used for data management and analysis. Results Over the previous three decades, stunting rates in boys under five have consistently been 4-7 percentage points (ppt) higher than those in girls of the same age. The prevalence of stunted children was greater in households with the lowest socioeconomic status (SES) (38.6%) compared to those with the highest SES (12.6%). Similar to the trend analysis, a multivariable regression analysis found that residency in the Southern Highlands (AOR = 2.368; 95% CI: 1.746-3.212, p < 0.001), male children (AOR = 1.583 [95% CI: 1.349 - 1.858], p < 0.001), low birth weight (AOR = 3.639 [95% CI: 2.279 - 5.810], p < 0.001), maternal exposure to alcohol (AOR = 1.440 [95% CI: 1.057 – 1.963], p < 0.05), and unimproved sanitation facilities (AOR = 1.345 [95% CI: 1.055 – 1.714], p < 0.05) were significantly associated with a higher risk of stunting. In contrast, a birth interval of 24 to 47 months (AOR = 0.762 [95% CI: 0.598 - 0.969], p < 0.001), a high level of maternal education (AOR = 0.715 [95% CI: 0.530 – 0.963], p < 0.05), and high socioeconomic status (AOR = 0.268 [95% CI: 0.178 – 0.403], p < 0.001) were significantly associated with a lower risk of stunting. Conclusion Although child stunting has decreased in the country, it remains a major challenge in Tanzania, driven by factors such as residing in the Southern Highlands, child and maternal issues, and household economic and environmental factors. To combat stunting and eliminate structural obstacles, including the empowerment of marginalised groups, a multisectoral strategy is required. Furthermore, current regulations and standards place more emphasis on educating mothers about diet and health than on empowering them economically.